Report from the First Snake Genomics and Integrative Biology Meeting - Castoe, Todd A. (Michigan State University, 2012)
This report summarizes the proceedings of the 1st Snake Genomics and Integrative Biology Meeting held in Vail, CO USA, 5-8 October 2011. The meeting had over twenty registered participants, and was conducted as a single session of presentations. Goals of the meeting included coordination of genomic data collection and fostering collaborative interactions among researchers using snakes as model systems.